Obstacle and Singularity Avoidance of Redundant Serial Manipulators Using the Concept of Task Priority - Arora, Himanshu (My University, 2014)
In this thesis work, the redundancy resolution of serial robot manipulators is performed. Redundant manipulators have the characteristics that there exists infinite solutions to the inverse kinematic problem. Out of those infinite solutions, it is possible to choose certain specific solutions on merit, which can be selected on the basis of some performance criteria or priority of some tasks over the other. These priority subtasks can be position prior to orientation, obstacle avoidance, singularity avoidance, torque minimization etc. Out of these parameters, this thesis is focused on obstacle and singularity avoidance using concept of task priority. This concept of task priority is implemented in relation to the inverse kinematics problem of redundant manipulators. A required task is divided into a number of subtask according to the order of priority. The redundancy resolution is performed to achieve the required working of manipulator under complex environment i.e. avoiding obstacle and singularity while tracing a given trajectory. The entire procedure is formulated using the pseudoinverse of the Jacobian matrix. A number of numerical simulation are performed for different complex environments consisting of obstacles with a given trajectories to show the efficacy of the redundancy control scheme for obstacle and singularity avoidance. Also to show the validity of the formulation, these cases are discussed further by tuning the parameters. An attempt has been made in this thesis to highlight the snakelike behavior of redundant manipulators, while tracking trajectories in very narrow channels. The snake-like behavior is important in many challenging applications like under-water welding in a narrow tanks, to check the blockage of sewerage pipes, to perform laparoscopy operation inside a human body etc.
ME, MED
Keywords: Obstacle Avoidance; Singularity Avoidance; Task Priority; Redundant Manipulators